2015
DOI: 10.2147/ppa.s92108
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with self-monitoring renal function after renal transplantation: results from a single-center prospective pilot study

Abstract: BackgroundAfter a kidney transplantation, patients have to visit the hospital often to monitor for early signs of graft rejection. Self-monitoring of creatinine in addition to blood pressure at home could alleviate the burden of frequent outpatient visits, but only if patients are willing to self-monitor and if they adhere to the self-monitoring measurement regimen. A prospective pilot study was conducted to assess patients’ experiences and satisfaction.Materials and methodsFor 3 months after transplantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Similar challenging conditions for training were found in a study of patients' experiences with training during admission in the early postoperative phase (Urstad, Wahl, Andersen, Øyen, & Fagermoen, 2012). The study identified that emotional, physical and drug-related aspects negatively affected patients' ability to concentrate and learn (Urstad et al, 2012).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar challenging conditions for training were found in a study of patients' experiences with training during admission in the early postoperative phase (Urstad, Wahl, Andersen, Øyen, & Fagermoen, 2012). The study identified that emotional, physical and drug-related aspects negatively affected patients' ability to concentrate and learn (Urstad et al, 2012).…”
Section: Discussionsupporting
confidence: 55%
“…Similar challenging conditions for training were found in a study of patients' experiences with training during admission in the early postoperative phase (Urstad, Wahl, Andersen, Øyen, & Fagermoen, 2012). The study identified that emotional, physical and drug-related aspects negatively affected patients' ability to concentrate and learn (Urstad et al, 2012). They found that the patients found it difficult to apply theoretical knowledge at home, as they had few experiences of transferring knowledge during admission (Urstad et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For example, a more directive, medical focused support style, typified by the 'Clinician' perspective described by van Hooft et al [26], may be more appropriate to use with patients in profile A. Similarly, a 'Coaching', holistic approach may be more appropriate with patients in profile B. Telemedicine [35] and home-testing of blood pressure and creatinine [36] may be most appreciated by patients in profile D+. We note however that, despite advances in eHealth to support selfmanagement, this patient population unanimously appreciated personal contact with professionals.…”
Section: Discussionmentioning
confidence: 99%
“…In a next step, it would be desirable to establish a cognitive and psychosocial rehabilitation plan to improve coping strategies and strengthen the patients’ resources in order to positively influence the final outcome of the transplant process. These efforts therefore must operate simultaneously at several levels on the basis of an integrated strategy that organizes and coordinates the various types of treatment-medication, psychotherapy, assistance-and the operators’ different functions, in an intervention program formulated on the basis of the characteristics and needs of each individual patient[43,44]. …”
Section: Discussionmentioning
confidence: 99%